Role of Dynamic Hip Screw in the Management of Trochanteric Fractures of the Hip - kumar, Dr. L. Prasanna; kumar, Dr. M. Vinod (RA Journal Of Applied Research, 2018)
A study of the management of trochanteric fractures of the hip using dynamic hip screw is carried out to note the difficulties (technical errors) and associated fracture complications arising out of its use, and to assess the functional results obtained in treating trochanteric fractures with DHS. Technical errors in terms of inadequate fracture reduction and poor placement of lag-screw and barrel plate are noted, associated deficiencies identified and preventary techniques evaluated. Fracture complications occurring in trochanteric fractures fixed with DHS with technical errors and without technical errors are recorded and the seriousness of the technical error estimated. Functional results in terms of pain, gait, range of movement, shortening and time taken to return to pre-injury functional status are assessed and overall functional results evaluated. This is mainly to confirm the efficacy of dynamic hip screw in fixing trochanteric fractures.